2017
DOI: 10.7554/elife.22706
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic switch controls intestinal differentiation downstream of Adenomatous polyposis coli (APC)

Abstract: Elucidating signaling pathways that regulate cellular metabolism is essential for a better understanding of normal development and tumorigenesis. Recent studies have shown that mitochondrial pyruvate carrier 1 (MPC1), a crucial player in pyruvate metabolism, is downregulated in colon adenocarcinomas. Utilizing zebrafish to examine the genetic relationship between MPC1 and Adenomatous polyposis coli (APC), a key tumor suppressor in colorectal cancer, we found that apc controls the levels of mpc1 and that knock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
4
15
0
3
Order By: Relevance
“…APC similarly regulates CtBP1 expression in human colon cancer cell lines [91], indicating that the zebrafish mechanism by which it drives differentiation through retinoic acid biosynthesis may be present in the human colorectal epithelium as well. Studies from the zebrafish model also indicate that impaired intestinal differentiation following Apc loss is mediated in part by a decrease in the expression of mitochondrial pyruvate carrier 1 ( Mpc1 ), resulting in defective pyruvate metabolism that is independent of the WNT pathway and potentially linked to the Warburg effect [94]. Since differentiation and cell migration along the crypt-villus axis are coupled processes [95], APC may help link cell fate and cell migration in the colorectal epithelium.…”
Section: The Role Of Apc In Differentiationmentioning
confidence: 99%
“…APC similarly regulates CtBP1 expression in human colon cancer cell lines [91], indicating that the zebrafish mechanism by which it drives differentiation through retinoic acid biosynthesis may be present in the human colorectal epithelium as well. Studies from the zebrafish model also indicate that impaired intestinal differentiation following Apc loss is mediated in part by a decrease in the expression of mitochondrial pyruvate carrier 1 ( Mpc1 ), resulting in defective pyruvate metabolism that is independent of the WNT pathway and potentially linked to the Warburg effect [94]. Since differentiation and cell migration along the crypt-villus axis are coupled processes [95], APC may help link cell fate and cell migration in the colorectal epithelium.…”
Section: The Role Of Apc In Differentiationmentioning
confidence: 99%
“…In particular, glycolysis was shown to be characteristic of 5 self-renewing stem cells and of different types of progenitors, such as neuronal and 6 hematopoietic progenitor cells [1,2]. It has been demonstrated that stem cells tend to 7 switch from glycolytic metabolism toward mitochondrial oxidative phosphorylation 8 (OXPHOS) while they differentiate [3][4][5]. Accordingly, it was suggested that a balance 9 between glycolysis and OXPHOS metabolism could somehow guide the choice between 10 self-renewal and differentiation in stem cells fate [6].…”
mentioning
confidence: 99%
“…Tiene una prevalencia de 1 cada 10.000 individuos y una incidencia en la población española de 2,8 por cada 100.000 habitantes (35). En la mayoría de los pacientes los pólipos empiezan a desarrollarse durante la segunda década de la vida y, en todos los casos, los pacientes sin tratamiento desarrollan tumores entre los 40 y los 50 años (36). El patrón de herencia para la PAF es autosómico dominante, por lo que en las familias portadoras de una mutación asociada a este síndrome existe una fuerte agregación, aunque aproximadamente un 25% de los casos son causados por mutaciones de novo (35).…”
Section: B) Poliposisunclassified
“…El 30% de las familias afectadas con PAFA no presentan mutaciones en el gen APC, pero presentan mutaciones en el gen MYH; en estos casos, el síndrome se denomina Poliposis Adenomatosa asociada al gen MYH (PAM) y presenta un patrón de herencia autosómico recesivo (36,39). Además de los síndromes mencionados anteriormente, en la tabla 3 se incluyen diferentes tipos de poliposis gastrointestinales asociados al riesgo de padecer CCR, dentro de los cuales se incluye el síndrome de Peutz-Jeghers, la Poliposis Familiar Juvenil y Poliposis Hiperplásica, el síndrome de Codwen y Poliposis asociada a los genes que codifican la DNA polimerasa.…”
Section: Figura 5 Colectomía De Un Paciente Con Paf Que Muestra Innunclassified
See 1 more Smart Citation